DAMPAK PELAKSANAAN KEBIJAKAN PENGHAPUSAN SANKSI PAJAK TERHADAP PENERIMAN PAJAK PENGHASILAN DAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI ( Studi Kasus di KPP Pratama Muara Bungo ) - Nurul Fadilah (Pt. Anagata Sembagi Education, 2024)
The main objective of this research is to determine the impact of implementing the policy of eliminating tax sanctions on income tax revenues and individual taxpayer compliance at KPP Pratana Muara Bungo.This type of research is a case study. Data was collected through documentation techniques. Data analysis in this research uses descriptive analysis. Income tax revenue is measured using a comparison from year to year. Registration compliance is measured using the percentage of additional registered WPOP. Payment compliance is measured using the additional percentage of taxpayers who make tax deposits on annual income tax returns for underpayments. The research results show that the implementation of the policy of eliminating tax sanctions does not have a partial impact on income tax revenues and individual taxpayer compliance. This can be seen from the low tax revenues in the year after the policy of eliminating tax sanctions was implemented and the low number of people applying for registration to eliminate tax sanctions as well as the low number of taxpayers who deposited tax on annual income tax returns for underpayments.